Vδ2 T-cells response in people with Mpox infection: a three-month longitudinal assessment - Eleonora Cimini; Eleonora Tartaglia; Francesco Messina; Andrea Coppola; Valentina Mazzotta; Massimo Tempestilli; Giulia Matusali; Stefania Notari; Annalisa Mondi; Gianluca Prota; Alessandra Oliva; Carla Fontana; et al. (Emerging Microbes and Infections)
The first evidence that Orthopoxvirus induced the expansion in vivo and the recall of effector innate Vδ2 T-cells was described in a macaque model. Although, an engagement of αβ T-cells specific response in patients infected with human monkeypox (Mpox) was demonstrated, little is known about the role of γδ T-cells during Mpox infection. IFN-γ-producing γδ T-cells in the resistance to poxviruses may a key role in inducing a protective type 1 memory immunity. We analyzed the kinetics of Vδ2 T-cell response from the acute phase up to three months after Mpox infection. Fourteen MSM subjects (5 PWH, 35.7%) were enrolled in a longitudinal study from May to July 2022. Blood samples were collected in the early phase of infection (T1, T2) and at 3 months (T3M) post-symptom onset. Vδ2 T-cell profiles (CD45RA/CCR7), activation/exhaustion markers (CD38/HLA-DR/CD57/PD-1/TIM-3), cytokine production (IFN-γ/TNF-α) and CD107a expression were assessed by multiparametric flow cytometry. Ten healthy donors (HD) were used as a control group. At T1, Vδ2 T-cell frequency of patients decreased, and effector memory Vδ2 T-cells increased with respect to HD. Activation/exhaustion markers were higher than HD. Vδ2 functionality decreased at T1 related to HD, and it was associated with CD38 and HLA-DR higher expression as well as TIM-3. Vδ2 T-cells restored their profile at T3M. The presence of effector/activated Vδ2 T-cells in the early stages of Mpox infection and their capability to activate quickly, producing pro-inflammatory cytokines, may be useful to enhance the early adaptive response to human Mpox, maintaining a protective memory/effector T-cell response.